ANGIOTENSIN II DI PERBENIHAN ADIPOSIT YANG DIPAJAN GLUKOSA TINGGI - Novi Khila Firani (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2013)
Abdominal obesity is closely linked to the occurrence of metabolic syndrome. In pathomechanism of metabolic syndrome, adipocity plays an important role as an active metabolic endocrine organ. This is accomplished the secretion of various hormones, enzymes, cytokines, and components that play a role in the rennin angiotensin system (RAS). One of the mechanisms linking the occurrence of hypertension in obesity is through the increased activity of RAS. Angiotensin II is the major effector of hypertension. The effect of high glucose exposure in adipocytes culture to angiotensin II secretion up to now is yet unknown. Adipociyties culture from rat visceral adipose tissue were exposed to 5 mM glucose concentration (as a physiological condition), 11 mM and 25 mM glucose concentration as the high glucose condition. Measurement of the angiotensin II level which is secreted in the culture medium was done by ELISA method. The mean (SD) levels of angiotensin II were 56.4 (4.28), 66.05 (2.24), and 69.22 (3:49) ng/mL respectively, for adipocities cultures exposed to 5 mM, 11 mM and 25 mM glucose concentration. High glucose exposure could increase the secretion of angiotensin II significantly in adipocytes culture. This suggests that the condition of hyperglycemia affects adipocytes dysfunction that play a role in the metabolic syndrome pathomechanism.